Bioaccumulation of Iron (Fe) in Sepat Fish (Trichogaster trichopterus) in Miai River Waters Banjarmasin City - Santoso, Heri Budi; Alivia, Nazillah; Muhamat, Muhamat (Jurnal Perikanan dan Kelautan, 2025)
Miai River is one of the rivers with various anthropogenic activities such as dense settlements, factories, and landfills. Industrial waste and domestic waste generated by residents are suspected to result in water contamination by toxic materials. Fe pollution is a major concern in aquatic ecosystems, especially in the Miai River of Banjarmasin City. This study aimed to evaluate the concentration of Fe in water and sepat fish and determine its relationship with fish weight. This research was conducted by taking samples of fish and water at 2 different locations and for testing the heavy metal content was analyzed by AAS. The results of Fe levels in river water at point 1 averaged 1.155 mg/L and at point 2 averaged 2.102 mg/L, exceeding the specified quality standards. The results of Fe levels in fish at point 1 averaged 26.450 mg/Kg and at point 2 averaged 22.466 mg/Kg exceeded the standard limit. The relationship between Fe in water and in fish is r = -0.999, meaning that the correlation is very strong and opposite. The relationship between Fe in fish and fish body weight is very low with a value of r = 0.164.